FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA KUNJUNGAN LANSIA KE POSYANDU LANSIA DI PUSKESMAS BATANG BERUH KECAMATAN SIDIKALANG KABUPATEN DAIRI - FRANS JUNIARDI (Welfare StatE, 2013)
One indicator of the success of development is the increasing life expectancy of the population. The increasing number of elderly people will also cause a variety of technical issues, such as medical, mental, psychological and socio-economic. To overcome these problems, the government program for the elderly integrated health centre improve the health and quality of health services elderly. This study aims to determine what factors affect the low posyandu elderly pensioners to visit in health center batang Beruh sub-district Sidikalang regency of Dairi This study uses descriptive research with a qualitative approach. Informants were selected using purposive sampling techniques, the number of informants in this research field is determined according to the adequacy of the data or information required in accordance with the objectives of the study. Data collection techniques used is literature and field study consisting of interviews and observations. The data analysis technique used is descriptive qualitative accurately describe the properties of an object subject or situation by collecting, managing, presenting and describing the results of the study as it is. Based on the results of data analysis that there are several factors that cause low posyandu visits to elderly seniors. These factors are knowledge of the elderly, distance between home and neighborhood health center location, facilities and inadequate infrastructure, lack of information about elderly neighborhood health center, the economy and income, lack of family support, attitudes and behaviors of the elderly are covered, and the other facilities provided by the government. Keywords: elderly, elderly integrated health centre